Patrystyczna interpretacja zakazu gniewu w Mt 5, 22a - Nieścior, Leon (Vox Patrum, 2023)
The radical condemnation of anger in Matthew 5:22 raises some fundamental questions: Does this first antithesis of the Sermon on the Mount actually interpret or change the Old Law? How is this radical prohibition of anger fulfilled? Is anger really put on the same level as murder? Is all anger banned? Collecting the answers to these fundamental questions of Greek and Latin early Christian writers, the author of the article reconstructs a patristic propaedeutic for a detailed interpretation of Matthew 5:22, and pays special attention to the contribution of St. Augustine in this field.